Role of Surveillance Colonoscopy With Mortality Event due to Colorectal Cancer and Cancer Stage Findings in Inflammatory Bowel Disease Patients - Akbar, Muhamad; Bhaskara, Rezdy; Wibowo, Bogi; Mubarak, Husni; Tama, Yhang; Faridah, Amirah (Clinical and Research Journal in Internal Medicine, 2024)
Background: Patients with Inflammatory bowel disease (IBD), both due to ulcerative colitis (UC) and Crohn’s disease (CD), are at higher risks of having colorectal cancer (CRC). Various guidelines have recommended surveillance using a colonoscopy. However, evidence of its usefulness for prognosis remains a subject of discussion. Aim: To determined the difference in mortality rate due to CRC and cancer stage between patients IBD who undergo routine surveillance and whoes do not. Methods: Studies performed searches on database of Science Direct, PUBMED, EBSCO, and Cochrane for research types of randomized controlled trials (RCTs), cohort, or case-controls that evaluate the role of surveillance on patients with IBD regarding to mortalities due to CRC and cancer stage findings. Data were then analyzed using the fixed/random effect model based on heterogeneity to evaluate the odds ratio (ORs) with a 95% confidence interval, calculated using the Mantel-Haenszel method. Results: Based on five observational studies that evaluated 3,215 patients with Inflammatory Bowel Disease by surveillance, compared with 4,465 control patients, it was found that patients undergoing surveillance have significantly lower mortality due to CRC (15.1%) than the control patients (23.8%) (OR 0.36 (95% CI: 0.24–0.52), p < 0.00001). There are more patients with end-stage colorectal cancer without surveillance (37%) than those with surveillance (20%) (OR 0.28 (95% CI: 0.20–0.41), p < 0.00001). Conclusion: Patients with inflammatory bowel disease who undergo routine colonoscopy surveillance will have a lower mortality rate and be found with earlier-stage cancer than patients who do not undergo routine colonoscopy examination.